INDONESIAN RURAL EFL TEACHER’S STRATEGY IN TEACHING HIGHER ORDER THINKING SKILLS - Novita Silta Pasutri; Bukhori Bukhori; Helmiati Helmiati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research aims to explore the rural teacher’s strategy in teaching Higher Order Thinking Skills based on the 2013 curriculum. By using qualitative approach, the researchers collect the data employs non-participant observation in the teaching and learning process, interviewed the English teacher, also documents by collecting the lesson plan made by one of the English teacher in one of Junior High School in Gaung District. The result of this research showed that the teacher used determining learning objectives with the eight characteristics of the lesson plan for 2013 curriculum, teach through questioning with LOTS questions, practice before assessment but it’s not effective, also provide assessment and feedback to develop students’ Higher Order Thinking Skills. The researchers also found that the teacher miss the step of review, refine and improve because she did not collect the students’ feedback. Based on the finding above, the researchers conclude that the teacher has been trying to do the steps to develop the students’ HOTS, but the development of HOTS in the rural area is not reach the expectation of the Higher Order Thinking based on 2013 curriculum.